Room : a novel - Donoghue, Emma, 1969- (Little, Brown and Co., 2010)
Narrator Jack and his mother, who was kidnapped seven years earlier when she was a 19-year-old college student, celebrate his fifth birthday. They live in a tiny, 11-foot-square soundproofed cell in a converted shed in the kidnapper's yard. The sociopath, whom Jack has dubbed Old Nick, visits at night, grudgingly doling out food and supplies. But Ma, as Jack calls her, proves to be resilient and resourceful--and attempts a nail-biting escape.